Mechanical model of the over-stroke displacement behaviour for double concave surface slider anti-seismic devices - Di Cesare, Antonio; Ponzo, Felice Carlo; Telesca, Alessio (Frontiers in Built Environment, 2022)
For double concave curved surface slider (DCCSS) isolators with a flat rim and lacking restrainers, such as those most commonly used in Europe, the rigid slider can exceed the geometrical capability of the housing plate during earthquakes stronger than those produced in simulations. During this over-stroke displacement, DCCSSs preserve the ability to support superstructure gravity loads and the capacity to dissipate energy. There are currently no applicable hysteresis rules or available algebraic solutions that can be used to predict over-stroke behaviour for response-history analysis. This study presents an algebraic solution to extend basic theories for estimating the actual limit displacement of DCCSS devices with over-stroke capacity. DCCSS behaviour in the over-stroke sliding regime was modelled with a focus on geometrical compatibility and kinematics. The proposed analytical formulation was calibrated on the basis of experimental controlled-displacement tests performed on single DCCSS devices. A case study of a six-storey reinforced concrete frame isolated building was modelled using a combination of non-linear elements that are currently available in several structural analysis software packages and able to correctly model over-stroke displacement behaviour for non-linear time history analyses. The DCCSS model was augmented with a friction model capable of accounting for torsional effects, axial load, and velocity variabilities. Comparison with non-linear dynamic analysis outcomes shows that the forces and displacements in the over-stroke sliding regime are predictable and therefore useful for the designer.